A stream ordering approach based on network analysis operations - Gulgen, Fatih (TAYLOR & FRANCIS LTD, 2017)
Stream ordering is a technique for characterizing the constituent parts of a drainage network. Network analysis remains one of the most popular and persistent research and application areas in geographic information science. In this study, a new stream ordering approach based on geographic information systems tools and network analysis operations is proposed. The new method combines the concepts of modern network analysis operations, which mainly deal with derivations of the best route solution, and the previous stream ordering techniques. In this context, the method readily identifies the channel heads hierarchically in order to derive main stream channel and its tributaries, and assigns a unique order for each stream on the network.
Keywords: GIS; stream ordering; channel network; the shortest path; OD matrix; CHANNEL NETWORKS; ALGORITHM; Environmental Sciences & Ecology; Geology; Remote Sensing; Imaging Science & Photographic Technology